INTEGRASI KESANTUNAN SOSIOLINGUISTIK DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Santoso, Tri; Kusmanto, Hari; Bilqis Salsabila S, Safa (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2025)
Language politeness among students is currently experiencing a reduction in polite language. The phenomenon of the reduction of students' language politeness in this educational environment needs attention and touch. One way that can be done to overcome the reduction of language politeness in the educational environment can be done by integrating language politeness in the pursuit of learning activities. This research is descriptive qualitative research with a combination of content analysis and literature review. The data and data sources in this study were taken from Merdeka curriculum documents published in the form of regulations from the Minister of Education, Culture, and Research of Indonesia. In addition, literature books and journals related to sociolinguistic politeness also became data sources in this study. The validation technique in the research used triangulation of data sources and theories. The data in this study were analyzed inductively based on Milles and Huberman's analysis technique. The results of this study revealed that teachers in integrating language politeness can use sociolinguistic politeness in early learning activities, core learning, and end of learning activities. Language politeness integration learning is basically a method used to foster students' ability to communicate in accordance with the context and situation of communication. In other words, the integration of sociolinguistic politeness in language learning as an effort to achieve the learning objectives in which students can use language as a means of communication. Language politeness assessment can be done with essay tests, observations, and objective tests.